AWARENESS OF BREAST CANCER SYMPTOMS IN IRAQI FEMALES ATTENDING PRIMARY HEALTH CARE CENTERS IN BAGHDAD AL KARKH DIRECTORATE2023-2024 (CAHIERS MAGELLANES-NS, 2024)
1.Background :Breast cancer is the most common cancer diagnosed in women, accounting for more than 1 in 10 new cancer diagnoses each year. It is the second most common cause of death from cancer among women in the world. Breast cancer evolves silently, and most disease is discovered on routine screening. This activity reviews the pathophysiology, presentation and diagnosis of breast cancer and highlights the role of screening and early diagnosis in its management.Aims of the study :To assess the level of  awareness about  signs ,symptoms , risk factors and age of presentation of breast cancer and  determine the association between awareness and certain variables among Iraqi females attending primary health care centers in Baghdad Health Directorate -Al-Karkh   2023-2024.Methods :A cross sectional study, a convienent sample for womens who attended primary health care centers for routine care visits or health problems and agree to participate in this study. The study will be conducted in Baghdad (alkarkh) primary healthcare  center from November 2023 to march 2024.Result : Age distribution is categorized into five groups, with the largest cohorts being 41-50 years and 51-60 years, each comprising 25% of the population. The youngest age group (21-30 years) constitutes 18.4% of the population, while the oldest age group (61-70 years) comprises 10%.Educational status is classified into Illiterate, Primary education, Secondary education, and College, with the majority (46.3%) having attained college education. Notably, 18.8% of the population is illiterate, Occupation-wise, the population is split between Housewives (48.1%) and Working individuals (51.9%),Residence status shows a majority in urban areas (76.9%) compared to rural areas (23.1%). Regarding family history of breast cancer, most individuals (96.3%) report no history, while a minority (3.8%) have a positive family history. Marital status reveals that the majority are married (76.9%), followed by unmarried (16.3%) and divorced (6.9%). Parity indicates a majority of multiparas (86.3%) compared to nulliparous individuals (13.8%). Breastfeeding history shows that the majority (62.2%) have breastfed, while a minority (37.8%) have not. lumps or thickening in the breast (248 "Yes" responses) and under the armpit (203 "Yes" responses), discharge from the nipple (253 "Yes" responses) and changes in nipple appearance (e.g., pulling in or change in position) (132 and 127 "Yes" responses, respectively), pain in one breast or armpit (250 "Yes" responses) is commonly associated with breast cancer.Conclusion:Cancer imposes a huge burden on people around the world.164 This study investigated the epidemiological aspects and the risk factors associated with breast cancer in the world. The trace of breast cancer as one of the most common form of cancer and causes of mortality among women is seen all over the world, and the mortality rate of breast cancer is higher in less developed countries.